Leveraging Remittances for Sustainable Growth in West African Monetary Zone: The Role of Institutional Quality - Ajileye, Bolaji Titilope; Anyanwu, Sarah Olanrewaju (International Journal of Economics and Financial Issues, 2025)
This study examines the role of remittances in stimulating West African Monetary Zone growth from 1990 to 2023, focusing on their interaction with institutional quality. Using the panel auto-regressive distributed lagged model, the study reveals that remittances significantly promote long-run growth, but poor institutional quality weakens its impact. Further, control of corruption and the economic freedom index enhance WAMZ growth. Based on these findings, WAMZ governments should channel remittances into productive investments, prioritise institutional reforms, and enforce consistent economic policies. Accordingly, these measures will aid in harnessing remittances for sustainable growth and foster the region’s resilience and competitiveness in the global economy.